Prevention Of Breast and Endometrial cancer using Total Diet Replacement (PROBE-TDR) trial: protocol for a randomised controlled trial. Issue 7 (19th July 2022) - Clarke, Helen; Harvie, Michelle; Lombardelli, Cheryl; Krizak, Suzanne; Sellers, Katharine; Harrison, Hannah; Lim, Yit Y; Parkin, Caroline; Patel, Shruthi; Issa, Basil G; Maxwell, Anthony J; Wisely, Julie; et al.
Abstract : Introduction: Obesity and overweight are strong potentially modifiable risk factors for postmenopausal breast and endometrial cancer. Bariatric surgery can achieve considerable weight loss and risk reduction of weight-related cancer but is unlikely to be a feasible cancer prevention strategy. Total diet replacement (TDR) can also lead to significant weight reduction. This study aims to examine the cellular and molecular changes in breast and endometrial tissue in high-risk women following TDR-induced weight loss, as well as longer-term adherence to a 12-month TDR weight loss intervention. Methods and analysis: PROBE-TDR (PR evention O f B reast and E ndometrial cancer using T otal D iet R eplacement) is a prospective, non-blinded, randomised controlled trial of 47 women at increased risk of breast and/or endometrial cancer. Randomisation is 2:1 to either an immediate 12-month TDR weight loss programme (n=31) or delayed dietary intervention (control) (n=16). The TDR programme includes an initial 12-week period of TDR (850 kcal/day) followed by a 40-week food-based diet, based on the nutritional principles of a Mediterranean diet, as either continued weight loss (~1500 kcal/day) or weight loss maintenance (~2000 kcal/day). Menstrual phase-matched biopsies of the breast and endometrium will be assessed at baseline and at the end of the 12-week TDR in the immediate diet group, compared with women randomised to the control group following their usual diet. The trial will also assess longer-term adherence and weight loss success across the 12-month programme in both the immediate and control groups. Ethics and dissemination: Approval for this study has been obtained from the Health Research Authority and Health and Care Research Wales (approval 20/NW/0095). Results will be published in peer-reviewed journals, presented at conferences and shared with trial participants. Trial registration number: International Standard Randomised Controlled Trial Number Registry (ISRCTN15358157 ).